2010
DOI: 10.1002/jbm.a.32677
|View full text |Cite
|
Sign up to set email alerts
|

Haemo‐ and cytocompatibility of bioresorbable homo‐ and copolymers prepared from 1,3‐trimethylene carbonate, lactides, and ϵ‐caprolactone

Abstract: A series of bioresorbable polymers were prepared by ring-opening polymerization of L-lactide (LLA), DL-lactide (DLLA), epsilon-caprolactone (CL) and 1,3-trimethylene carbonate (TMC), using low toxic zinc lactate as catalyst. The various PLLA, PTMC, PCL homopolymers, and PLLA-TMC, PDLLA-TMC, PCL-TMC copolymers with 50/50 molar ratios were characterized by using analytical techniques such as proton nuclear magnetic resonance, gel permeation chromatography, tensiometer, and differential scanning calorimetry. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…The polymer films were prepared with the method of heated-melt and mould fixation as previously reported [15][16][17][18]. The three kinds of polymer materials and 10% (w/v) dichloromethane were melted into collosols by heating and cast into the culture capsules, and fixed into the films with dimensions of 0.4 mmÂ10 mmÂ10 mm overnight, respectively.…”
Section: Polymer Film Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymer films were prepared with the method of heated-melt and mould fixation as previously reported [15][16][17][18]. The three kinds of polymer materials and 10% (w/v) dichloromethane were melted into collosols by heating and cast into the culture capsules, and fixed into the films with dimensions of 0.4 mmÂ10 mmÂ10 mm overnight, respectively.…”
Section: Polymer Film Preparationmentioning
confidence: 99%
“…In our previous reported work, various homo-and copolymers were synthesized from L-lactide, D, L-lactide, trimethylene carbonate, and e-caprolactone. Among them, PDLLA-TMC and PLLA-TMC present favorable in vitro degradable behavior, good cyto-compatibility, and mechanical properties [15][16][17][18]. In this work, we studied the in vivo degradation and histocompatibility of PLLA/TMC and PDLLA/TMC copolymers to explore the feasibility of manufacturing fully biodegradable cardiovascular stents.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have claimed that the copolymerization of L ‐lactide ( L LA) with 1,3‐trimethylene carbonate (TMC) can be a successful route to modify both mechanical properties and biodegradation rate of P L LA . Hence, some copolymers based on L LA and TMC have been realized and used in commodity as high‐performance medical biomaterials …”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Hence, some copolymers based on LLA and TMC have been realized and used in commodity as high-performance medical biomaterials. [29][30][31][32][33] In previous work, we have investigated PTMC-LLA copolymers synthesized by random copolymerization with different compositions and chain structures. [34][35][36] It appears that the incorporation of TMC component significantly enhances the toughness and reduces the acidity of degradation products compared with pure PLLA.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [6] reported that hemolysis tests showed that all homopolymers and copolymers presented very low hemolytic ratios, indicating good hemolytic properties. Adhesion and activation of platelets were observed on the surface of polylactic acid, polycaprolactone (PCL), poly L-lactic acid (PLLA) and trimethylene carbonate (TMC) (PLLA-TMC), and poly-DL-lactide (PDLLA)-TMC films, while fewer platelets and less activation were found on poly(TMC).…”
mentioning
confidence: 99%